Indoleamine-2,3-Dioxygenase as a Perioperative Marker of the Immune System - Bello, Corina; Heinisch, Paul Philipp; Mihalj, Maks; Carrel, Thierry; Luedi, Markus M. (Frontiers in Physiology, 2021)
Indoleamine-2,3-dioxygenase (IDO) is the “rate-limiting” enzyme in the kynurenine (Kyn) pathway of the tryptophan (Trp) catabolism. By its immune-modulatory effect, IDO initiates changes to the physiologically balanced immune state and plays a key role in pathogenesis of various diseases, as well as in the perioperative setting during surgery. In autoimmune processes, highly malignant cancers such as glioblastoma or organ transplantation, IDO’s involvement has been studied extensively. However, in severe systemic infections, as present in sepsis, it is not yet completely understood. Hereafter, we review the current knowledge of IDO’s implication on such complex immune-related processes. Moreover, we address the role of IDO as a predictive biomarker as well as therapeutic target for immune-mediated diseases. Finally, we discuss IDO in the setting of surgical trauma induced stress and highlight its promising use as a biomarker in the pre-operative setting for all disciplines involved in the decision-making process and treatment of patients undergoing surgery.